2021
DOI: 10.3324/haematol.2020.272419
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for endocrine complications in transfusion-dependent thalassemia patients on chelation therapy with deferasirox: a risk assessment study from a multi-center nation-wide cohort

Abstract: Transfusion-dependent patients typically develop iron-induced cardiomyopathy, liver disease, and endocrine complications. We aimed to estimate the incidence of endocrine disorders in transfusion-dependent thalassemia (TDT) patients during long-term iron-chelation therapy with deferasirox (DFX).We developed a multicentre follow-up study of 426 TDT patients treated with once-daily DFX for a median duration of 8 years, up to 18.5 years. At baseline, 118, 121, and 187 patients had 0, 1, or ≥2 endocrine diseases re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 39 publications
1
28
1
Order By: Relevance
“…Endocrine disorders are currently the most frequent complications and those with the greatest impact on the quality of life of subjects affected by haemoglobinopathy, with a risk of developing a new endocrine complication after five years equal to approx. 10%, even in subjects with a good control of their iron balances [ 1 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Endocrine disorders are currently the most frequent complications and those with the greatest impact on the quality of life of subjects affected by haemoglobinopathy, with a risk of developing a new endocrine complication after five years equal to approx. 10%, even in subjects with a good control of their iron balances [ 1 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hypogonadotropic hypogonadism is the most frequent complication, together with bone metabolism disorders, in adult women with transfusion-dependent haemoglobinopathy, reaching prevalences of over 50% in historical cohorts, and lower but still relevant prevalences in more recent cohorts [ 1 , 16 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Thalassemia International Federation Study Group on Growth and Endocrine Complications reported that hypogonadism was the most common endocrinopathy (40.8%), closely followed by growth retardation (30.8%) with hypothyroidism being the least common (3.2%) in 3817 patients with thalassemia major (TM) [1]. Another study in 426 patients with TM showed that the risk of developing an endocrine complication was 9.7% in 5 years, despite adequate chelation [2].…”
Section: Introductionmentioning
confidence: 99%